Penerapan Model Pembelajaran Think Pare Share Dalam Upaya Meningkatkan Kemampuan Pemecahan Masalah Matematika Siswa di SMP Negeri 5 Angkola Timur - Sari, Puspa Indah; Harahap, Haritsah Hammamah; Mandopa, Andi Saputra (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
The problem in this research is an affort to improve students’ mathematical problem-solving abilities at SMP Negeri 5 Angkola Timur in the matter of a system of two-variable linear equations in class VIII by applying the Think Pair Share learning model. This type of research is Classroom Action Research. The research subjects are class VIII students of SMP Negeri 5 Angkola Timur. The object taken in this research is problem-solving skills by applying the Think Pair Share learning model. From the results of the cycle test, the lowest score was 30 and the highest score was 80. There were 12 students who scored <65 (46.15%) and 14 students who scored ≥ 65 (53.85%). ). As well as the average value obtained on the initial test is 59,26. After giving action in cycle II for two meetings through the stages of applying Think Pair Share learning model, at the end of the lesson given a problem solving ability test to students, the class average value is 71,42 in the second cycle test, it was seen that 23 students (88,46) had completed their studies and 3 students (11,54) did not complete their studies. Keywords— mathematic, problems solving, Think Pair Share